Investigation of the effects of hot dip aluminizing and diffusion annealing on microstructural and tribological properties of dual phase (DP800) steels - Yürektürk, Yakup; Çeltik, Cansu (Pamukkale Üniversitesi, 2024)
In this study, the effects of hot dip aluminizing (HDA) (90 s at 725°C) and diffusion annealing on the microstructural and tribological properties of DP800 steel were investigated. After HDA treatment, one of the sample was left to cool in air (HDA-1) and the other one left to cool in air after being subjected to a diffusion annealing for 1 hour in an oven set at 300°C (HDA-2). Evolution in mechanical and tribological properties depending on the developments in the coating microstructure investigated in terms of hardness and wear behaviour, respectively. Mechanical characterization results show that diffusion annealing increases the hardness value of hot dip aluminized steel to 1100 HV values. Considering the wear ball volume and friction coefficients, the most advanced tribological properties were observed in the diffusion-annealed HDA process (HDA-2).

Bu çalışmada, sıcak daldırmalı alüminyumlama (HDA) (725°C'de 90 sn.) ve difüzyon tavlaması işleminin DP800 çeliğinin mikroyapısal ve tribolojik özellikleri üzerindeki etkileri incelenmiştir. HDA işleminden sonra numunelerden biri havada (HDA-1), diğeri ise 300°C'ye ayarlanmış fırında (HDA-2) 1 saat difüzyon tavlaması işlemine tabi tutularak havada soğumaya bırakılmıştır. Kaplama mikroyapısındaki dönüşüme bağlı olarak değişen mekanik ve tribolojik özellikler sırasıyla sertlik ve aşınma davranışı bakımından incelenmiştir. Mekanik karakterizasyon sonuçları, difüzyon tavlaması işleminin sıcak daldırma alüminize çeliğin sertlik değerini 1100 HV değerlerine çıkardığını göstermektedir. Aşınan bilye hacmi ve sürtünme katsayıları dikkate alındığında en gelişmiş tribolojik özellikler difüzyon tavlaması işlemi görmüş HDA prosesinde (HDA-2) gözlenmiştir.
Sıcak daldırma alüminyumlama ve difüzyon tavlaması işleminin çift fazlı (DP800) çeliklerin mikroyapısal ve tribolojik özelliklerine etkilerinin incelenmesi
Keywords: Mechanical Engineering (Other); Makine Mühendisliği (Diğer)